The Functional Characteristics of Teacher Talks In English Classroom - Muh. Sahlim (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2017)
The aim of this research is to identify functional characteristics of English teacher talks when delivering material in English classroom for target students in Makassar Islamic University. The design of this research is descriptive qualitative. The data are obtained from talks of four teachers through observation, recording, interview and field notes. The teacher talks are carefully transcribed. The data are analyzed by categorizing the teachers’ talks to find out the functional characteristics of the talks. The research indicated nine functional characteristics of teacher talks: introducing material, correcting, repeating, explaining, defining, giving example, clarifying, questioning and encouraging. Each functional characteristic is employed to make the teaching process meaningful for the students’ comprehensions.